An optimization of energy cost of clean hybrid solar-wind power plants in Iran. Issue 15 (8th December 2019) - Jahangiri, Mehdi; Nematollahi, Omid; Haghani, Ahmad; Raiesi, Heidar Ali; Alidadi Shamsabadi, Akbar
ABSTRACT: Given the available capacities in Iran in terms of wind and solar renewable energies and regarding the fact that, to achieve a high economic growth, Iran needs to rise its power generation capacity, as well as considering that Iran suffers from severe shortage of water sources and necessarily needs to produce electricity without consuming water, this study aimed to find the lowest cost of energy generation by hybrid solar-wind system in 103 stations in Iran, using data taken from NASA and HOMER. Since building sector accounts for 45% of energy consumption in Iran, our purpose was to supply the electricity of an off-grid residential building. Results revealed that there is a high potential for using solar and wind renewable energies in Iran, so that the lowest and highest percentages of using renewables were recorded at Darab with 87% and Jask stations with 100% usage. Furthermore, the highest and lowest price per kWh of power generated were associated with a solar-diesel generator-battery system at Darab station with a price of 0.75/kWh and a wind-diesel generator-battery system at Bandarabbass station with a price of 0.586/kWh. Authors hope these results could play an effective role in development of using renewable energies in Iran.